Integrating soil physical property management to foster chemical and biological resilience in sustainable crop systems - Vikraman, S U; Sheeba, S; Saravana, P P; Amutha, R; Sharmila, R C (Plant Science Today, 2025)
The favourable physical (such as texture, structure, bulk density, porosity and water holding capacity), chemical (including pH, cation exchange capacity and EC) and biological (like microbial diversity, soil respiration and enzyme activity) traits are regarded as defining features of healthy soil, which is critical for productive and sustainable crop production. Soil health and quality are significantly influenced by these physical, chemical and biological characteristics. The physical properties of soil, such as texture, structure and bulk density, play a pivotal role in determining water holding capacity, nutrient retention, nutrient cycling, root penetration, aeration, drainage and microbial activity all of which are interconnected for sustainable agriculture. Soil quality can be improved through the application of various soil amendments, which are materials derived from organic, inorganic, or biological sources and are aimed at enhancing soil productivity and overall characteristics. Amendments such as cover crops, farmyard manure, vermicompost and biochar have demonstrated significant effects such as reducing bulk density and increasing porosity in various soil textures, including silt loam, clay loam and sandy loam. Similarly, conservation tillage practices, particularly under organic management systems, have been shown to improve soil physical properties compared to conventional tillage by increasing infiltration rates, reducing penetration resistance and enhancing soil structure stability. These practices also positively impact chemical and biological soil properties such as improving nutrient availability, boosting microbial diversity and enhancing soil organic carbon sequestration. By fostering a supportive environment for plant growth, such integrated soil management approaches lead to higher crop yields while promoting long-term soil sustainability and resilience.